Study protocol of a pilot randomized controlled trial of transcranial direct current stimulation paired with reappraisal training for treatment of cannabis use disorder - Adam M. Stryjewski; Tammy J. Chung; Li Yan McCurdy; Tara L. Spitzen; Kangxin Zhang; Kristen P. Morie; Vaughn R. Steele; Michael J. Crowley; Marc N. Potenza (PLoS ONE, 2025)
Introduction As legalization of cannabis products continues, cannabis use becomes more prevalent, and concerns regarding cannabis use disorder (CUD) rise, improving CUD treatment has become increasingly important. Techniques used to regulate emotions, such as cognitive reappraisal, may help manage cravings for cannabis in individuals with CUD. Transcranial direct current stimulation (tDCS), a noninvasive brain stimulation technique, may improve regulation of emotions and reduce substance use. This study aims to determine whether the addition of tDCS to training in cognitive reappraisal leads to greater reductions in cravings and cannabis use than cognitive reappraisal without active stimulation. Methods and analysis This longitudinal between-subjects study will recruit 60 participants who will each be randomly assigned to receive either active or sham tDCS. Participants will undergo 5 sessions, each spaced approximately one week apart. In session, they will receive 20 minutes of (active/sham) 1.5mA anodal stimulation over the right dorsolateral prefrontal cortex while receiving training in cognitive reappraisal. Primary outcomes include changes in cannabis use during the study, changes in electroencephalogram brain activity when viewing cannabis cues, and changes in cannabis craving intensity. Discussion The results of this study will inform a full-scale randomized controlled trial designed to assess the effectiveness of this intervention. More broadly, these results will add to the literature on the role of tDCS in enhancing CUD treatment. Trial registration ClinicalTrials.gov NCT06369311